The effect of work discipline and work motivation on employee performance at the Ros Hotel in Yogyakarta - Sanjaya, Muhammad Taufiek Rio (Institute of Accounting Research and Novation (IARN), 2023)
This study aims to determine: (1) the level of work discipline, work motivation, and employee performance at the Ros In Hotel Yogyakarta, (2) the effect of work discipline on the performance of the Ros In Hotel Yogyakarta employees, (3) the effect of work motivation on the performance of the Ros In Hotel employees Yogyakarta, and (4) the effect of work discipline and work motivation on the performance of Hotel Ros In Yogyakarta employees. This research includes causal associative research using a quantitative approach. The population in the study were 115 employees of Hotel Ros In Yogyakarta. The sample technique used was purposive sampling so that a sample of 115 people was obtained. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results of the study at a significance level of 5% show that: (1) The work discipline level of Hotel Ros In Yogyakarta employees is in the moderate category (62.4%), the work motivation of Hotel Ros In Yogyakarta employees is in the moderate category (78.8%), and the performance Ros In Hotel Yogyakarta employees in the moderate category (62.4%); (2) Work Discipline has a positive and significant effect on the performance of Hotel Ros In Yogyakarta employees. This is evidenced by the results of the regression calculation, which obtained a value of (β) 0.340 (**p<0.05; p=0.000).